Strategi Peningkatan Kinerja SDM di Waralaba “Kopi Titik Koma” The Hok Jambi - Anaseputri Jamira; Fachruddin Razi; Muhammad Amali; Yulita Febriani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to formulate a strategy for improving the performance of Human Resources (HR) at The Hok Coffee Shop "Kopi Titik Koma" - Jambi City by using SWOT Analysis. Direct interviews, surveys, and observations were used to obtain data which were then analyzed using the SWOT method. The results of this study show that integrative strategies and SO (Strengths and Opportunities) strategies that can be used include developing performance through workshops, collaborating with partners, and maximizing promotions to customers. This research is still limited to the IE Matrix. In the future, a series of strategic management analysis tools can be used to obtain more optimal input for making management decisions.